Isolation, purification and identification of ellagic acid derivatives, catechins, and procyanidins from the root bark of Anisophyllea dichostyla R. Br. - Khallouki, Farid; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut; Owen, Robert (Food and chemical toxicology, 2007)
The root bark of Anisophyllea dichostyla R. Br. is traditionally used in the Democratic Republic Congo for the treatment of several conditions such as anorexia, fatigue and intestinal infections. We have identified and quantitated several polyphenol antioxidants in the methanol extract of the root bark (120g). The polyphenol content (3.32g/kg) was predominantly ellagitannins (25%) and polyhydroxyflavan-3-ols (catechins and procyanidins, 75%) with 3′-O-methyl-3,4-methylenedioxo ellagic acid 4′-O-β-d-glucopyranoside and (-)-epicatechin as the major species in each class. These two compounds and the following species were identified unequivocally by NMR spectroscopy: (+)-catechin, (−)-epicatechin 3-O-gallate, 3-O-methyl ellagic acid, 3,3′-di-O-methyl ellagic acid, 3′-O-methyl-3,4-methylenedioxo ellagic acid, 3′-O-methyl-3,4-methylenedioxo ellagic acid 4′-O-β-d-glucopyranoside, and 3′-O-methyl ellagic acid 4-O-β-d-xylopyranoside. The following additional compounds were purified by semi-preparative HPLC and tentatively identified on the basis of UV spectra, HPLC-ESI-MS and nano-ESI-MS-MS: (+)-catechin-3-O-β-d-glucopyranoside, epicatechin-(4β→8)-catechin (procyanidin B1), epicatechin-(4β→8)-epicatechin (procyanidin B2), an (epi)catechin trimer, 3-O-methyl ellagic acid 4-O-β-d-glucopyranoside, (-)-epicatechin 3-O-vanillate, 3,4-methylenedioxo ellagic acid 4′-O- β-d-glucopyranoside, and 3,3′-di-O-methyl ellagic acid 4-O-β-d-xylopyranoside. Fractionation of the raw extract by column chromatography on silicic acid yielded 10 fractions. In the hypoxanthine/xanthine oxidase antioxidant assay system, CC-9 which contained a range of polyphenols dominated by (−)-epicatechin-O-gallate proved to be the most potent antioxidant fraction (IC50=52μg/mL) in terms of ROS scavenging. In terms of XO inhibition CC-8, dominated by (epi)catechin trimer and which also contained appreciable amounts of 3′-O-methyl ellagic acid 4′-O-β-d-xylopyranoside, as well as the catechins (+)-catechin-3-O-β-d-glucopyranoside, epicatechin-(4β→8)-catechin (procyanidin B1), and (−)-epicatechin 3-O-gallate, proved to be the most potent (IC50=36μg/mL).